Factors influencing acculturative stress among international students in the United States - Eustace, Rosemary William (Kansas State University, 2007)
The purpose of this study was to determine the factors influencing acculturative stress among international students from the international student perspective. This study explored how acculturative stressors, social support and stress are related. In addition the study examined the significant socio-cultural and demographic predictors of acculturative stress. The Berry's acculturation stress research framework and Bronfenbrenner's ecological perspective were used to guide this study. Data was collected using an online survey from international students across a cohort of eleven U.S universities. Of the 986 students who took the survey, only complete data from 606 students were included in the current study. Descriptive statistics, univariate and multivariate statistical analyses were employed to summarize and test the proposed hypotheses. The findings indicated that students who were experiencing increased levels of difficulty with the acculturative stressors were more likely to experience higher levels of stress. In addition international students who reported high levels of collective social support were more likely to display less impact of acculturative stressors on acculturative stress. However, the unique moderating influences of various types of social support (family, friends and important others) on the relationship between acculturative stressor and stress was not supported. The findings on the socio-cultural and demographic predictors of acculturative stress suggested that using the assimilation mode and identifying marital status in the "others" category was indicative of lower stress. Lower income and self identified lower social class prior and during acculturation were predictive of higher acculturative stress levels. Findings highlight the fundamental role of the international student's social context and its impact on his/her acculturation process and outcomes. The findings have implications for professionals and scholars who work with international students in practice, education and policy. Suggestions for future research are also included.
Keywords: Acculturative stress; International students; Acculturation; Sociology, Individual and Family Studies (0628)